2018
DOI: 10.1128/iai.00388-18
|View full text |Cite
|
Sign up to set email alerts
|

MrpJ Directly Regulates Proteus mirabilis Virulence Factors, Including Fimbriae and Type VI Secretion, during Urinary Tract Infection

Abstract: is a leading cause of catheter-associated urinary tract infections (CAUTIs) and urolithiasis. The transcriptional regulator MrpJ inversely modulates two critical aspects of UTI progression: fimbria-mediated attachment and flagellum-mediated motility. Transcriptome data indicated a network of virulence-associated genes under MrpJ's control. Here, we identify the direct gene regulon of MrpJ and its contribution to pathogenesis, leading to the discovery of novel virulence targets. romatinmmunorecipitation followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…In several pathogens, such as Yersinia pseudotuberculosis, Proteus mirabilis , and Vibrio cholerae , the QS system is the main regulatory mechanism of bacterial competence via T6SS, which is involved in the invasiveness and motility that favor the development of bacteraemia (Zhang et al, 2011; Debnath et al, 2018; Jaskólska et al, 2018; Trastoy et al, 2018). Moreover, in 86% of ICU patients, gastrointestinal tract colonization by a clinical strain of A. baumannii led to development of bacteraemia caused by genetically similar strains (Thom et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In several pathogens, such as Yersinia pseudotuberculosis, Proteus mirabilis , and Vibrio cholerae , the QS system is the main regulatory mechanism of bacterial competence via T6SS, which is involved in the invasiveness and motility that favor the development of bacteraemia (Zhang et al, 2011; Debnath et al, 2018; Jaskólska et al, 2018; Trastoy et al, 2018). Moreover, in 86% of ICU patients, gastrointestinal tract colonization by a clinical strain of A. baumannii led to development of bacteraemia caused by genetically similar strains (Thom et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…mirabilis in mouse model experiments; this may be due to dysfunctional MR/P fimbrial production or assembly when mrpH is expressed from a plasmid, or, more likely, because the chromosomal mrpH mutation is polar on mrpJ . MrpJ is a transcriptional regulator that controls levels of multiple known and predicted virulence factors, including flagella, MR/P and other fimbriae, and a type VI secretion system [ 28 , 49 ]. Further study will be needed to tease apart the separate roles of MrpH and MrpJ during UTI.…”
Section: Resultsmentioning
confidence: 99%
“…mutation is polar on mrpJ. MrpJ is a transcriptional regulator that controls levels of multiple known and predicted virulence factors, including flagella, MR/P and other fimbriae, and a type VI secretion system [28,49]. Further study will be needed to tease apart the separate roles of MrpH and MrpJ during UTI.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Here, the presence of Proteus mirabilis and Klebsiella pneumoniae in this commensal community correlated with colitogenic potential (Garrett et al, 2010). Both of these species possess T6SSs that display antibacterial activity (Alteri et al, 2013;Hsieh et al, 2019), while this secretion system has also been shown to contribute to the fitness of the pathogens in vivo (Lery et al, 2014;Debnath et al, 2018). One can therefore contemplate a role for this secretion system in the TRUC model whereby T6SS-mediated elimination of commensal bacteria promotes an inflammatory response that cannot be restrained due to the immune genes deficiency of the host, resulting in colitis.…”
Section: T6ss Deployment By Bacterial Pathogens: Upsetting the Applecartmentioning
confidence: 86%